A New Approach to Improve Transmitting and Receiving Timing in Orthogonal Frequency Division Multiplexing (OFDM) Systems - Ghassan A. Abed (Iraqi Journal for Computer Science and Mathematics, 2023)
Nowadays, most wireless communications employ OFDM technology to reduce signal interference. Its sensitivity to timing faults, however, can cause a severe performance reduction. This study suggests a new approach to enhance communication systems' transmitting and receiving time. Although OFDM is a widely used modulation strategy in communication systems, it is vulnerable to timing faults, which can seriously affect performance. A frequency interference processing method is created that uses OFDM technology and goes through numerous steps, such as correcting CFO, adding a periodic prefix to prevent frequency distortion, calculating the time delay between transmission and reception, and spotting timing mistakes. It is clear that the lack of synchronization between the transmitter and channel interference has caused the Signal-to-Noise Ratio (SNR) to decline correspondingly. The initial approach had a piece of code that computed the transmission and reception times while recording their differences. As a result, it handles signal interference and frequency and temporal synchronization, two key aspects of OFDM. Timing precision varies from 0 to 1, and the time gap between transmission and reception is only a fraction of a second. When the SNR was available, timing errors and the lag between transmission and reception timing were seen, which suggests that there is a small probability of having too many locks or losing codes while utilizing OFDM. Simulation exercises show that the suggested method considerably enhances the system's Bit Error Rate (BER) performance in a variety of time offset conditions. The outcomes imply that the suggested strategy could be a workable remedy for OFDM systems with timing issues.